Author Correction: Variants in exons 5 and 6 of ACTB cause syndromic thrombocytopenia. Issue 1 (December 2018) - Latham, Sharissa; Ehmke, Nadja; Reinke, Patrick; Taft, Manuel; Eicke, Dorothee; Reindl, Theresia; Stenzel, Werner; Lyons, Michael; Friez, Michael; Lee, Jennifer; Hecker, Ramona; Frühwald, Michael; et al.
The original version of this Article contained an error in Figure 4. In panel i, the lower CYA and α-SMA images were inadvertently inverted. This has been corrected in both the PDF and HTML versions of the Article.